Maturation characteristics, embryo development and onset feeding of Sultan Fish, Leptobarbus Hoevenii - Sajeenuth Srithongthum (2020)
Sultan fish, Leptobarbus hoevenii is an important freshwater cyprinid for aquaculture in several Southeast Asian countries, including Thailand and Malaysia. However, there is limited knowledge on the length-weight relationship, reproductive characteristics, egg and larval biology of this fish. Therefore, the present study was conducted to examine: 1) length-weight relationship (LWR) of the broodstock, 2) reproductive characteristics including gonado-somatic-index (GSI), fecundity, and egg diameter, 3) egg development and hatching timing, and 4) yolk sac absorption, mouth development, and the first exogenous feeding of L. hoevenii. In Experiment 1, a total of 95 ponds farmed L hoevenii broodstock (35 females and 60 males) were examined. The b value of the females was 3.10 (> 3.0), indicating that they have attained positive allometric growth. In opposite, the males and the overall populations have attained negative allometric growth as their b value was 2.66 and 2.92 (<3.0), respectively. All of these LWRs were significant at a = 0.01 with their correlation coefficient (r) values at 0.88 0.90. However, the 95% confidence intervals of these b values were in the range of 2.32 - 3.64; they included 3.0 and overlapped each other. This result showed that these b values were not significantly different, indicating that the fish has achieved ideal growth. In Experiment 2, 40 pond-farmed L. hoevenii broodstock (20 for each female and male) were obtained to measure their GSI. Ten females were randomly sampled from the 20 to determine their fecundity. Totally 1,500 eggs were sampled from each female; the egg diameter was measured and statistically analyzed following the Bhattacharya's method and normal probability plot analysis to confirm whether L. hoevenii is a single- or multiple spawner. The total length (TL) and body weight (BW) of the female L. hoevenii were 32.2- 47.1 cm and 350 - 1,200 g, respectively. All females contained ovaries, and the GSI was 1.81 - 12.28 %. The fecundity was 35, 467 - 128,067 eggs; the highest fecundity was observed in a 1,000 g fish. The TL and BW of the male fish were 30. 7-- 45.8 cm and 180 - 970 g, respectively. Testes were found in all males, and the GSI was 1.03 - 5.09 %. The observed egg diameter was very variable, ranging from 500 to 1,855 um. Following the Bhattacharya's method and normal probability plot analysis, 4- 5 and 2 - 5 groups of egg class were detected hence it was confirmed that the L. hoevenii is a multiple-spawner. In Experiment 3, artificial breeding of L. hoevenii was conducted to obtain the egg samples. The temperature of water was 28 ± 1 °C, it was determined that the egg fertilization ratio was 85.4 ± 1.01 %; the egg developed through the cleavage period, morula and gastrula stages, the segmentation periods, and the complete embryo formed 18 hrs 11 minutes after fertilization (AF); some newly hatched were already seen at this stage. The egg hatching event completed 22 hrs and 44 minutes AF, and the hatching ratio was 87 ± 8.92 %. In Experiment 4, it was determined that the yolk sac volume of the newly hatched L. hoevenii larvae was 77.51 ± 9.6 m, and it completely absorbed at 108 hAH (hours after hatching). The larval mouth has first opened at 36 hAH (mouth height 215 ± 22.59 m) but the larvae only commenced first exogenous feeding on Moina (approximately 207 μm in width) at 62 hAH, when its mouth height reached 372.91 ± 79.11 μm. The L. hoevenii larvae required about 18 hrs from 62 - 80 hAH, to adapt themselves to feed on the given Moina, and the "Point of No Return" was estimated to happen at 70 - 72 hAH. Therefore, it was recommended that Moina should be given to the L. hoevenii larvae best within 62- 72 hAH at the rearing water temperature of 27 °C to 29 C.